MR defecography for obstructed defecation syndrome - Thapar, Ravikumar B; Patankar, Roysuneel V; Kamat, Ritesh D; Thapar, Radhika R; Chemburkar, Vipul (Indian Journal of Radiology and Imaging, 2015)
Patients with obstructed defecation syndrome (ODS) form an important subset of patients with chronic constipation. Evaluation and treatment of these patients has traditionally been difficult. Magnetic resonance defecography (MRD) is a very useful tool for the evaluation of these patients. We evaluated the scans and records of 192 consecutive patients who underwent MRD at our center between January 2011 and January 2012. Abnormal descent, rectoceles, rectorectal intussusceptions, enteroceles, and spastic perineum were observed in a large number of these patients, usually in various combinations. We discuss the technique, its advantages and limitations, and the normal findings and various pathologies.
Keywords: Chronic constipation; magnetic resonance defecography; obstructed defecation syndrome; pelvic floor